Systematic identification of the chemical components of leaves and roots of Didymocarpus heucherifolius Hand.-Mazz. based on UHPLC Q-Exactive Orbitrap MS technology coupled with molecular networking strategy - Liangyin Shu; Shunli Xiao; Kailin Li; Huibin Luo; Meng Li; Qingrui Yang; Bowen Gao; Jiaxin Li; Fang Yan; Wei Cai (Scientific Reports)
Abstract Didymocarpus heucherifolius Hand.-Mazz. is plant of the genus Didymocarpus wall. (Gesneriaceae). Species in this genus have long been used in folk medicine to treat various illnesses, including wounds, kidney stones, inflammations, asthma, influenza, etc. However, there are few studies on chemical components. Crude plant extracts are a complex mixture of several biologically active specialized metabolites. Therefore, a rapid and accurate identification and quantification are critical in phytochemical analysis. An efficient approach based on molecular networking strategy coupled with ultra high-performance liquid chromatography coupled with Q-Exactive Orbitrap tandem mass spectrometry (UHPLC Q-Exactive Orbitrap MS) was used to analyze the chemical components systematically. The chemical was identified using retention time, accurate molecular weight, parent peaks, fragment peaks, fragmentation characteristics, comparative analysis with the literature, reference standards, and standard databases, including mzVault. A total of 108 compounds (32 phenylpropanoids, 14 phenolic acid, 6 fatty acids, 14 organic acid, 9 flavonoid, 15 amino acids, and 28 other components) were identified in the leaves and roots of D. heucherifolius in which 84 and 84 compounds were found in the leaves and roots, respectively. The results showed that 68 components were different in plant roots and leaves, and these compounds were mainly represented in organic acids. Moreover, 50 identical chemical compounds were identified in plant roots and leaves, and these compounds were mainly phenylpropanoid compounds. The UHPLC Q-Exactive Orbitrap MS method was used for the first time to accurately, quickly, and systematically identify the compounds of the roots and leaves of Didymocarpus heucherifolius Hand.-Mazz., thereby providing a theoretical basis for its quality control, in-depth research, and further development.